The Variation of antioxidant activity profile of Dendrophthoe pentandra (L.) Miq. leaves extract from two varieties of mangoes (Mangifera indica) - Aditiyarini, Dwi; Elsa, Yohana; Restiani, Ratih (Jurnal Biologi Udayana; Vol 28 No 2 (2024): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2024.v28.i02.p13, 2025)
Mistletoe is a hemiparasites plant that interfere the growth of their host plant, However, mistletoe itself can be used in the herbal medicine. One of the cultivated plants is Indonesia which is affected by this mistletoe is mango. Mangoes is rich in antioxidant, so that its mistletoe is also thought to rich in antioxidant. This study is aimed to analyze the secondary metabolites and antioxidant activity of mango mistletoe from two varieties of mangoes, namely Harumanis and Madu. The study has been carried out experimentally. Samples were collected from Caturtunggal, Sleman, Yogyakarta. Extraction was carried by maceration in methanol. Phytochemical screening, quantitative analysis of phenolics compound and quercetin were performed using HPLC. Antioxidant activity was determined using DPPH method. Data was analyzed through descriptive statistisc. The result showed that the quercetin level and total phenolic compound of D.pentandra leaves extract from M.indica var. Madu are higher than var. Harumanis, which are 257.917 ppm and 399,195 ± 12.352 mg GAE/g extract respectively. Antioxidant activity of D.pentandra extract from M.indica var. Madu is also higher than var. Harumanis, with IC50 37.19 ppm. In this study, enviromental factor did not affect the secondary metabolites of mistletoe. Through this data, the difference of secondary metabolites profile and the antioxidant activity of mistletoe from different host varieties were found, particularly in quercetin and its phenolic compounds.